Dinamika dan Masa Depan Qanun dalam Mewujudkan Kesejahteraan Masyarakat Aceh - Ayon Diniyanto; Dani Muhtada (Ministry of Home Affairs, 2022)
After two decades of implementation of the special autonomy in Aceh, with Islamic Sharia becoming part of its legal system, some of Aceh's problems prevailed, especially those related to people's welfare. Whether the special autonomy granted to Aceh can improve the welfare of the people remains questionable. As a legal instrument in Aceh, the Qanun seemed to be unable to improve the people's welfare. Despite having enacted Qanun Number 11 of 2013 on Social Welfare, Aceh is still one of the ten poorest regions in Indonesia. This raises questions about the effectiveness of the Qanun in improving the welfare of the people. As such, this study is important to be carried out to find out the relevance of Qanun in improving the welfare of the people in Aceh. This study aimed to answer these questions: (1) What are the roles of Qanun in Aceh's special autonomy era? (2) What is the future of Qanun in creating welfare in Aceh? The purpose of this study was to (1) describe the role of Qanun in Aceh’s special autonomy era, and (2) predict the future of Qanun in creating welfare in Aceh, as well as provide recommendations to solve problems related to the ineffective implementation of Qanun. This study used a qualitative approach, and the type of this research was normative-juridical. The focus of the study was the special autonomy in Aceh and the role of Qanun in improving the people's welfare. Data were taken from primary and secondary legal materials using literature reviews. A triangulation was used to check the validity of the data, and the interactive model was used to analyze the data. This study found that Aceh already has several Qanuns regulating matters related to the welfare of the people. However, to attain a prosperous future for the people of Aceh, more Qanuns regulating various aspects of the economy are needed.